Legal Discourse and Cultural Meaning in a Bangka Manuscript: Insights for English Language Learning - Rakerda, Hilda; Amalia, Resti (Journal of English Language and Education, 2026)
Historical legal manuscripts from peripheral regions remain underexamined in English language studies, despite their value as authentic discourse and cultural evidence. This study addresses this gap through an analysis of a nineteenth-century Bangka legal manuscript documenting a local trade transaction. Drawing on critical discourse analysis and interviews to validate the manuscript’s historical context, the study identifies salient features of legal discourse, including formulaic phrasing, performative utterances, and culturally grounded constructions of authority and legitimacy. These features demonstrate legal language as a socially situated practice shaped by local norms and institutional relations. The study further highlights pedagogical implications for English language learning, positioning historical legal texts as authentic materials for developing genre and discourse awareness, intercultural understanding, and critical reading skills.